An Exploration into the Development of Cultural Heritage Research from an East Asian Regional Perspective - Ye, Wanjun (Transactions on Social Science, Education and Humanities Research, 2026)
Long-standing cultural exchanges rooted in Confucian civilization have left China, Japan and the ROK abundant homologous tangible and intangible cultural heritage. This focuses on East Asia to sort out research progress and facilitate regional collaborative protection. Based on the 2024 UNESCO heritage data and the annual bulletins of the cultural and museum departments of China, Japan, and South Korea, this study selected literature from CNKI, J-STAGE, and RISS databases from 2004 to 2024 and conducted a comparative analysis using literature statistics. According to statistics, the three countries own 94 world cultural & mixed heritage sites and 90 UNESCO Intangible Cultural Heritage inscriptions, ranking top across the Asia-Pacific region; Over the past two decades, academic research has shifted beyond mere textual research on ancient buildings, and more and more scholars are focusing on practical content such as digital filing and active operation of intangible cultural heritage. The differences in protection standards among countries, difficulties in obtaining evidence of cross-border intangible cultural heritage, and imbalances in the allocation of grassroots scientific research resources restrict the advancement of cross-national research. This article summarizes the achievements and existing shortcomings from five research dimensions, including historical tracing and national practices.
Keywords: East Asian Perspective; Cultural Heritage Research; Protection Practice; Regional Cooperation; Digital Transformation.